PERANAN H MUHAMMAD AMIN HUSIN DALAM MERINTIS KEMERDEKAAN RI DI PEKANBARU TAHUN 1916-1945 - Audy Ristaudy; Tugiman Tugiman; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: H Muhammad Amin Husin is one of figure who is pioneering freedom in Pekanbaru. H Muhammad Amin Husin has an important role in pioneering independence in Pekanbaru. The purpose of this research is, 1) to know the life history of H Muhammad Amin Husin, 2) to know how is role of Hajj Muhammad Amin Husin in Sarekat Islam, 3) to know what is role thet Haji Muhammad Amin Husin as the pioneer of independence in Pekanbaru , 4 to know the obstacles faced by Haji Muhammad Amin Husin to pioneer independence in Pekanbaru. The method used in this study is historically, a qualitative descriptist. The result of this study was H Muhammad Amin Husin once accompanied his brother who served as Datuk Bendahara Muda Sekijang Tapung Kanan became the scribe of the Kingdom of Siak. H Muhammad Amin Husin The originator of establishment of the Islamic Union branch of Siak Kingdom in Pekanbaru and served as Vice voorzitter of Islamic Sarikat in Pekanbaru. H Muhammad Amin Husin attempted to pioneer independence in the Malay world by planning a rebellion against the Dutch and also established PIM in Malaysia which aims to oppose the colonialism in the Malay world. In an attempt to pioneer independence there is a barrier to be experienced by H Muhammad Amin Husin, especially in the spirit of community nationalism in the midst of opposition and strict supervision of the colonial government.Key Words: H Muhammad Amin Husin, The pioneer of independence